Juegos verbales y la comunicación oral en niños de la Institución Educativa Inicial N°343 Corazón de Jesús, Ramón Castilla 2024 - Mozombite Sugaya, Eugenia Isabel (2025)
The purpose of this research was to determine the relationship between the level of application of verbal games and the level of oral communication in children of the Institución Educativa Inicial N°343 Corazón de Jesús, Ramón Castilla 2024. In this study, a research approach based on quantitative methods. The non-experimental research design was applied, adjusting a transectional correlational model. The population under study consisted of 76 children. The technique applied to collect information was observation, using an observation guide as an instrument. Which were validated by three experts in the field, resulting in the value of the Student's t statistic being 8.978, with a p-value (bilateral significance) of 0.000, which is less than 0.05. This allowed us to reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha) with a significance level of 5%. In this way, it was concluded that there is a statistically significant relationship between verbal games and the development of oral communication in children.